Evaluation of the influence of biological pretreatment with fungi (Pleurotus Ostreatus) in the improvement of alcoholic fermentation of mango residues (2019)
The excessive use of fossil fuels that generate greenhouse gases and that are increasingly difficult to extract endanger different ecosystems and the energy future in various parts of the world. For this reason, interest in the production of biofuels such as bioethanol has increased. Following that, the main objective of this study is to determine the influence of biological pretreatment with Pleurotus ostreatus in the alcoholic fermentation of mango residues, to evaluate the production of reducing sugars, the enzyme activity of the enzymes Laccase, Exopolygalacturonase and Exoglucanase, to determine the efficiency of ethanol production and to establish the influence of the amount of the substrate on the efficiency of ethanol production from the alcoholic fermentation of mango residues. For that reason, it was made a Pleurotus ostreatus inoculum in a 5L bioreactor at 150 rpm at 25°C for 10 days, in which two levels were evaluated: 10 and 20 g of dried mango per liter and a fermentation in 1L amber bottles for 10 days with Saccharomyces bayanus yeast. The importance of the enzymatic activity of exopoligalacturonase and glucanase at the reactor scale at the established conditions was verified and no laccases activity was detected. A biomass degradation was observed in both levels, but no significant effect was detected in any of the response variables of interest.